2003
DOI: 10.1124/jpet.103.056655
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Absorption of Recombinant Hirudin-2 in Rats

Abstract: To investigate the absorption of recombinant hirudin-2 (rHV2) after oral administration to rats and its possible absorption mechanism, a series of experiments were carried out. The degradation of 125

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Hirudin possesses valuable therapeutical potential as anticoagulant and antithrombotic agent because it is the most potent thrombin-specific inhibitor so far known and does not inhibit other enzymes in the blood coagulation or fibrinolytic pathways (Sohn et al 2001). Interestingly, hirudin can be taken orally (Yan et al 2004;Cen et al 2006). To test whether hirudin can be expressed in the food-grade bacterium L. lactis for oral administration, HV3 gene was fused to SP310mut2 signal peptide sequence (Ravn et al 2003), and extracellularly secreted in the food-grade lactic acid bacterium L. lactis by using a nisin-controlled gene expression system.…”
Section: Introductionmentioning
confidence: 99%
“…Hirudin possesses valuable therapeutical potential as anticoagulant and antithrombotic agent because it is the most potent thrombin-specific inhibitor so far known and does not inhibit other enzymes in the blood coagulation or fibrinolytic pathways (Sohn et al 2001). Interestingly, hirudin can be taken orally (Yan et al 2004;Cen et al 2006). To test whether hirudin can be expressed in the food-grade bacterium L. lactis for oral administration, HV3 gene was fused to SP310mut2 signal peptide sequence (Ravn et al 2003), and extracellularly secreted in the food-grade lactic acid bacterium L. lactis by using a nisin-controlled gene expression system.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, considerable effort has been directed towards developing alternative administration routes other than injection. Although recombinant hirudin-1 (rHV1) and rHV2 can be absorbed in the gastrointestinal tracts of rats after duodenal and oral administration, the absorption was limited or it varied depending on the analytical methods used, which indicated that the results were unreliable [6,7] . As a convenient method of administration, nasal delivery has many benefits relative to oral administration, including the avoidance of the liver first-pass effect and a higher bioavailability.…”
Section: Introductionmentioning
confidence: 99%
“…That is comparable to the representative highyield of rHV2-Lys 47 in S. cerevisiae (500 mg l -1 ), which was reached by fed-batch cultivation for 57 h [14], and 1.5 g l -1 of secreted rHIR in methylotrophic yeast P. pastoris, which was achieved by fed-batch cultivation for 65 h after methanol induction [18,23]. However, it can be seen that the long cultivation period is absolutely needed for attaining high level of expression with the yeast system, and this will inevitably increase the preparation cost and complexity of manufacturing.…”
Section: Discussionmentioning
confidence: 91%